Clinical perspectives on the use of the GIP/GLP-1 receptor agonist tirzepatide for the treatment of type-2 diabetes and obesity - Gallwitz, Baptist (Frontiers in Endocrinology, 2022)
Incretin based therapies with glucagon-like peptide-1 receptor agonists (GLP-1RA) are already established in the treatment of type 2 diabetes. The development of novel dual- or triple incretin receptor agonists binding to the receptors not only for GLP-1 but also to the receptors for glucose-dependent insulinotropic peptide (GIP) and/or glucagon has advanced and has lead to the approval of the GIP/GLP-1-receptor agonist tirzepatide for the treatment of type-2-diabetes (T2D) by the Food and Drug Administration (FDA) in the USA by once weekly subcutaneous injections. Tirzepatide dose dependently leads to clinically significant reductions in glycaemic parameters and body weight and has shown to have stronger effects in reducing these parameters than standard antidiabetic therapy. This article summarizes the current clinical study programme and the respective outcomes and highlights further potential indications for tirzepatide in the treatment of obesity and potentially other comorbidities of T2D.